Two wheels to freedom : the story of a young Jew, wartime resistance, and a daring escape - Magida, Arthur J. (Pegasus Books, 2024)
Though Cioma Schonhaus was only 11 years old when the Nazis first came to power, his cleverness and resourcefulness eventually made him an unlikely hero and bon vivant. As a young adult staying one step ahead of the S.S., Cioma would dine in swanky restaurants and frequent trendy bars and have plenty of romances--all while sabotaging weapons in the munitions factory where he worked. He even bought a sailboat and taught himself how to sail. These hijinks never distracted Cioma from a deeper mission. Trained as an artist, Cioma's masterfully forged fake IDs ensured that several hundred Jews survived the war. When he learned the Gestapo was closing in on him, Cioma masterminded a singularly daring escape: spending a month biking to Switzerland, he became the only person to cycle his way out of the Third Reich.